2000
DOI: 10.1021/jp000337n
|View full text |Cite
|
Sign up to set email alerts
|

NMR Characterization of Mesostructured Aluminophosphates

Abstract: The atomic structure of ordered mesostructured aluminophosphates with dodecyl phosphate as the structuredirecting template was investigated by multinuclear solid-state NMR. Two different types of materials were studied: one with the template headgroup as the only phosphate source and one where additionally phosphoric acid was used in the synthesis. All 31 P and 27 Al NMR resonances can be subdivided into three groups depending on the sample composition. Furthermore, 2D heteronuclear correlation NMR measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…In the latter case, the alkyl chain is decomposed at a higher temperature (200°C) and the sulfate group at a lower temperature (250°C) indicating a strong interaction between the sulfate head group and the alumina framework when the DS is occluded. This conclusion is similar to that obtained for lamellar aluminophosphates synthesized in the presence of mono-ndodecyl phosphate [33][34][35]. Indeed, it was clearly showed that the phosphate head group of the surfactant was embedded within the alumina framework, leading to the formation of an aluminophosphate.…”
Section: Study Of the Mechanism Of Formation Of A Mesostructured Aluminasupporting
confidence: 89%
“…In the latter case, the alkyl chain is decomposed at a higher temperature (200°C) and the sulfate group at a lower temperature (250°C) indicating a strong interaction between the sulfate head group and the alumina framework when the DS is occluded. This conclusion is similar to that obtained for lamellar aluminophosphates synthesized in the presence of mono-ndodecyl phosphate [33][34][35]. Indeed, it was clearly showed that the phosphate head group of the surfactant was embedded within the alumina framework, leading to the formation of an aluminophosphate.…”
Section: Study Of the Mechanism Of Formation Of A Mesostructured Aluminasupporting
confidence: 89%
“…3), suggests that the majority of the Al species are tetrahedral coordination Al(OP) 4 groups [23,24]. The 31 P MAS NMR spectra of the two calcined samples exhibit a strong signal centered at À 24 ppm, which can be mainly attributed to 4-fold coordinated P with O -Al [23,24]. The relatively broad resonance may be partly caused by the presence of a small amount of P species coordinating with H 2 O or OH groups, and may also imply the amorphous characteristic of the pore wall.…”
Section: Resultsmentioning
confidence: 99%
“…31 P magic-angle spinning (MAS) NMR has been used to probe the local environment around P, and for a number of these mesostructured AlPO materials, their 31 P MAS spectra usually exhibit multiple peaks, indicating the existence of different P local structures. 3a,c,f,4c,d, 5,10 The spectral assignments usually begin with a comparison of the observed 31 P chemical shifts with those reported for AlPO 4 -based three-dimensional microporous materials whose 31 P chemical shift values often fall in the range of -19 to -30 ppm. 3a,11 As previously mentioned, in those AlPO 4 -based materials, the P sites only have one type of P chemical environment, P(-OAl) 4 .…”
Section: Introductionmentioning
confidence: 99%